Aldosterone and Its Blockade: A Cardiovascular and Renal Perspective - V. Lahera; V. Cachofeiro; G. Balfagon; J.L. Rodicio (The Scientific World Journal)
Aldosterone not only contributes to salt and water homeostasis, but also exerts direct cardiovascular and renal effects. Numerous experimental and clinical studies indicate that aldosterone participate in cardiac alterations associated with hypertension, heart failure, diabetes and other pathological entities. It is important to mention that dietary salt is a key factor in aldosterone-mediated cardiovascular damage, since damage was moreevident in animals on a high-salt diet than animals on a low salt diet. A pathophysiological action of aldosterone involves development of extracellular matrix and fibrosis, inflammation, stimulation of reactive oxygen species production, endothelial dysfunction, cell growth and proliferation. Many studies showed local extra-adrenal production of aldosterone in brain blood vessel, and the heart, which contribute in an important manner to the pathological actions of this mineralocorticoid.Several studies such as RALES, EPHESUS, 4E and others, recently showed that mineralocorticoid-receptor (MR) antagonists, alone or in combination with ACE inhibitors or ARBs, reduced the risk of progressive target organ damage and hospitalization in patients with hypertension and heart failure. These clinical benefits support the therapeutic usefulness of MR antagonists.